Listening | the open ”“ music as disruptive topological experience (Dramaturgies, 2019)
This article reflects on the relation between music body(ies)1, body(ies) of music2 and notions of musical ‘space-time’ in the composition and performance process of Listening | the open, a trilogy for disruptive bodies, by Joana Sá. Bringing into discussion new possible notions of space of music as both intrinsic and extrinsic dimensions of music body(ies), and of the body(ies) of music, it proposes approaching music as a disruptive topology. Presenting strategies that are beyond the dualities of control/out of control, self/other, it emphasizes the fragment or fragmentation as a crucial basic topological event for triggering the musical processes.